Computational forensics 4th international workshop, IWCF 2010, Tokyo, Japan, November 11-12, 2010, revised selected papers - Sako, Hiroshi; Franke, Katrin Y.; Saitoh, Shuji (Lecture notes in computer science, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 4th International Workshop on Computational Forensics, IWCF 2010, held in Tokyo, Japan in November 2010. The 16 revised full papers presented together with two invited keynote papers were carefully selected during two rounds of reviewing and revision. The papers cover a wide range of current topics in computational forensics including authentication, biometrics, document analysis, multimedia, forensic tool evaluation, character recognition, and forensic verification.